An Analysis of Production Capacity of Mocaf Flour Product at karunia Maha Cipta, Bandung - Muhshi, Faikar Fadhlul; Simatupang, Togar M (Journal of Business and Management, 2014)
The development of food technology, produces flour from cassava which has similar characteristics to wheat flour called as mocaf (modified cassava). Karunia Maha Cipta as mocaf producer in Bandung has labelled their product as Mocaf Bandung. An analysis of business models regarding these products have been done to determine the position of Karunia Maha Cipta in the mocaf flour industry. Actual data from product sales until production process from last few months was used to analyze and modelling the existing system. Based on business model analysis, the market share for Mocaf Bandung too small only covers small-scale food industry and households. Root cause analysis showed that root causes were: insufficient production capacity, no backup machine, no market analysis and disobedient supplier. The posibble solutions that have been made are: increasing production capacity with three alternatives there is adding more production schedule, purcashing new machine, mixed between purchasing new machine and adding more schedule; new raw material regulations system for supplier, and do market analysis. The result of proposed solution is predicted to increase the production capacity by 119% and increase in profit by 265%.Keywords: Production Capacity, Business Model Canvas, Mocaf, Production Process, Capital Budgetting, Sensitivity Analysis, Root Cause Analysis.